Molecular Evolution of Antigen-Processing Genes in Salamanders: Do They Coevolve with MHC Class I Genes? - Palomar, Gemma; Dudek, Katarzyna; Wielstra, Ben; Jockusch, Elizabeth L; Vinkler, Michal; Arntzen, Jan W; Ficetola, Gentile F; Matsunami, Masatoshi; Waldman, Bruce; Těšický, Martin; Zieliński, Piotr; Babik, Wiesław (Genome biology and evolution, 2021)
Proteins encoded by antigen-processing genes (APGs) prepare antigens for presentation by the major histocompatibility complex class I (MHC I) molecules. Coevolution between APGs and MHC I genes has been proposed as the ancestral gnathostome condition. The hypothesis predicts a single highly expressed MHC I gene and tight linkage between APGs and MHC I. In addition, APGs should evolve under positive selection, a consequence of the adaptive evolution in MHC I. The presence of multiple highly expressed MHC I genes in some teleosts, birds, and urodeles appears incompatible with the coevolution hypothesis. Here, we use urodele amphibians to test two key expectations derived from the coevolution hypothesis: 1) the linkage between APGs and MHC I was studied in Lissotriton newts and 2) the evidence for adaptive evolution in APGs was assessed using 42 urodele species comprising 21 genera from seven families. We demonstrated that five APGs (PSMB8, PSMB9, TAP1, TAP2, and TAPBP) are tightly linked (<0.5 cM) to MHC I. Although all APGs showed some codons under episodic positive selection, we did not find a pervasive signal of positive selection expected under the coevolution hypothesis. Gene duplications, putative gene losses, and divergent allelic lineages detected in some APGs demonstrate considerable evolutionary dynamics of APGs in salamanders. Overall, our results indicate that if coevolution between APGs and MHC I occurred in urodeles, it would be more complex than envisaged in the original formulation of the hypothesis.
Keywords: molekulární evoluce; Caudata; geny MHC třídy I; Evolution, Molecular; coevolution; zvířata; MHC; proteiny obojživelníků; Gene Duplication; PSMB lineages; Urodela; Amphibian Proteins; Genes, MHC Class I; Genetic Linkage; Antigen Presentation; duplikace genu; molecular evolution; genetická vazba; Animals; salamanders; antigen-processing genes; prezentace antigenu